THE INFLUENCE OF TRADE PAYABLES AND TAXES PAYABLES ON LIABILITIES AT PT. STEEL PIPE INDUSTRY OF INDONESIA TBK LISTED ON THE INDONESIAN SHARIA STOCK INDEX (ISSI) FOR THE 2014-2024 PERIOD - Ki Agus Ahmad Jauhar Lisanulhak; Husni Rofiq (Lobi, 2025)
The Companies face increasingly complex challenges in financial management. Many elements inside and outside the company affect financial performance, so that more careful and efficient financial management is needed. Among the most important conditions of a company's financial structure are the obligations that must be met to maintain business continuity and comply with applicable regulations. The conceptual framework of this study explains that there is a positive impact between Trade Payables & Taxes Payables on Liabilities, which means that changes in the ratio value affect the increase or decrease in liabilities. Furthermore, this conceptual framework also shows that Liabilities are affected by other elements that are not the focus of this study. Internal factors include the company's capital structure, profitability level & debt policy. External factors include interest rates, inflation, government policies, market conditions, and competition. The research method used in this study is a descriptive method with a quantitative approach. The types and sources of data used in this study are secondary data sources obtained from the financial statements of PT. Steel Pipe Industry of Indonesia Tbk for the period 2014–2024, the official website.